Avaliação das vias aéreas superiores após uso do aparelho Herbst, por meio de sobreposição tridimensional - Palomino-Gómez, Sandra Patricia [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Changes in nasal breathing pattern affect the craniofacial growth. Technological advances, such as Cone beam computed tomography (CBCT), have been used in order to observe three-dimensionally (3D) the skull, face and pharyngeal airway space. The latter, with possible assessment of airway changes induced by orthopedic activators. The aim of this study was to evaluate the changes of the upper airway space resulted from mandibular advancement with Herbst appliance through superposition method of mathematical 3D coordinates. The sample was composed of 24 patients, 10 females and 14 males (16.1 years at the start of treatment - T1) treated for 8 months with Herbst appliance, and compared with a group control composed of 7 females (13.54 yrs at T1). Individuals of the samples were patients with malocclusion Class II division 1, already been through the pubertal growth spurt. The growth sprunt was assessment with hand/wrist radiographs. For each patient, CBCT scans were performed in two stages. The initial phase was conducted by location and identification of 79 anatomical points in the shaft, axial, coronal and sagittal views. Twenty-six anatomical points (skull base, maxilla, vertebra and Hyoid jaw) were adopted for the final analysis using Avizo analysis software®. After calibration of the examiner, each variable was measured three times. The statistical analysis was performed using Levene Test and t-Test with   39   significance level of 5%. The reliability of the measurements showed good reproducibility (ICC ≥ 0.92), exception were the top edge of cervical vertebra 3 and lower border of the Choanae. The results indicated statistical significance in axis Z for PNS (p = 04) compared to control group and for to tip of the epiglottis (p=0.02) compared with control group. Other structures, which were statistically significant, were the left portion of the greater cornu of hyoid...(Complete abstract electronic access below)

As mudanças nos padrões de respiração nasal afetam profundamente o crescimento craniofacial. Avanços tecnológicos, como a tomografia computadorizada de feixe cônico (TCFC), têm sido utilizados com o propósito de se observar tridimensionalmente a localização de diferentes estruturas do crânio, a face e o espaço aéreo faríngeo. Desta forma, é possível avaliar as alterações do espaço aéreo induzidas pelos aparelhos ortopédicos propulsores mandibulares. O intuito deste estudo foi avaliar as mudanças na faringe superior resultantes do avanço mandibular com aparelho Herbst, mediante análise do método de sobreposição de coordenadas tridimensionais matemáticas. A amostra deste estudo está composta por 24 pacientes, 10 do gênero feminino e 14 do gênero masculino (16,1 anos no início de tratamento), tratados por 8 meses com aparelho Herbst, sendo comparados com o grupo controle composto de 7 pacientes do gênero feminino (13,54 anos ao início do T1). Todos os indivíduos apresentavam má oclusão classe II divisão 1ª e já haviam passado pelo surto de crescimento pubertário (avaliados e pareados com radiografia de mão e punho). Os exames tomográficos foram realizados em dois tempos para cada paciente. A fase inicial foi realizada com a localização e identificação de 79 pontos anatômicos nos eixos: axial, coronal e sagital, sendo que 26 pontos anatômicos (base do crânio, maxila, mandíbula   37   vértebra e hióide) foram adotados para a análise final com auxílio do software AVIZO®. Após o processo de calibração, cada variável foi mensurada três vezes. A análise estatística dos dados foi realizada por meio do Test de Levane e teste T de Student ao nível de significância de 5 %. A confiabilidade das medidas apresentaram boa replicabilidade (ICC ≥ 0,921), com exceção da borda superior de vértebra cervical 3 e dos pontos inferiores da coana... (Resumo completo, clicar acesso eletrônico abaixo)
Evaluation of the upper airways after use of the Herbst appliance, via superposition of tridimensional images
Keywords: Tomografia Computadorizada de Feixe Cônico; Aparelhos ortopédicos; Nasofaringe; Ortopedic appliances; Nasopharynx